EVALUATION OF WASTE MANAGEMENT ACHIEVEMENT IN PADANGTEGAL PEKRAMAN VILLAGE, UBUD SUB DISTRICT, GIANYAR DISTRICT, BALI - I Made Wahyu Widyarsana; Kania Salmaa (Universitas Trisakti, 2019)
Aim: This study aims to evaluate the practice of waste management system conducted by community and business units in one traditional village in Bali and to discover the contributing factors to the success of the practice. Methodology and Results: A set of waste sampling method, observation, and interview were conducted to collect the basis data for the data calculation and analysis. The results show that the waste generation in Padangtegal Village currently reaches 38.18 m3/day or 1145.41 m3/month, with the largest weight composition from leaves and twigs waste (39.87%), food waste (29.07 %), and plastic (13.11%). With 100% of waste handling service, the processing of waste carried out in the area only reached 5.06% of 3R behavior (reduce, reuse, and recycle) at the source, and 1.10% composting at the composting house (Rumah Kompos). Conclusion, significance and impact study: Most of the processing carried out at Temesi Recycling is through composting (33.98%) and recovery of recycled material (33.68%), resulting in a residue (26.19%) which is transported to the Suwung Landfill. It could be concluded that organic waste processing through composting and recycling non-organic waste could reduce waste volume transported to the landfill about 67%.